1988
DOI: 10.1007/bf00339607
|View full text |Cite
|
Sign up to set email alerts
|

Precise excision of bacterial transposon Tn 5 in yeast

Abstract: We have demonstrated that precise excision of bacterial transposon Tn5 can occur in the yeast, Saccharomyces cerevisiae. Tn5 insertions in the yeast gene LYS2 were generated by transposon mutagenesis made in Escherichia coli by means of a lambda::Tn5 vector. Nine insertions of Tn5 into the structural part of the yeast LYS2 gene situated in a shuttle episomal plasmid were selected. All the plasmids with a Tn5 insertion were used to transform yeast strains carrying a deletion of the entire LYS2 gene or a deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…These results support the conclusion that the increase of reversion frequency in Text mutants is due to an increase of precise excision frequency. Previously (Gordenin et al, 1988) we confirmed the proposal about the precise excision of Tn5-13 based on restriction analysis by DNA sequencing.…”
Section: Selection Of Mutants With Increased Frequency Of Tn5 Excisiosupporting
confidence: 84%
See 2 more Smart Citations
“…These results support the conclusion that the increase of reversion frequency in Text mutants is due to an increase of precise excision frequency. Previously (Gordenin et al, 1988) we confirmed the proposal about the precise excision of Tn5-13 based on restriction analysis by DNA sequencing.…”
Section: Selection Of Mutants With Increased Frequency Of Tn5 Excisiosupporting
confidence: 84%
“…The deletion of the BamHI-XhoI fragment, DS(BX), was generated in this work; other deletions have been described by Chernoff et ai. (1984) and Gordenin et al (1988).…”
Section: Strains and Plasmidsmentioning
confidence: 98%
See 1 more Smart Citation
“…[Previously, we reported precise excision of Tn5-13 based on sequencing a limited number ofLYS2 revertants of a lys2::TnS insertion mutation located on a multicopy YEp plasmid (7).] Among seven independent Lys+ Adp+ isolates examined, all arose from imprecise excision (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore introduced TnM into the yeast Saccharomyces cerevisiae and examined excision from the L YS2 gene (7). The low excision rate (10-9) was increased 100-fold in tex mutants (8).…”
mentioning
confidence: 99%